High titanium slag aggregate concrete mix proportion design method based on aggregate characteristics
Through the design method of high titanium slag aggregate concrete mix ratio based on aggregate characteristics, the problem of limited application of high titanium slag aggregate in concrete is solved, and the optimization of concrete performance and design efficiency are achieved.
Patent Information
- Application Number
- CN202411508712.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-07
AI Technical Summary
The existing technology is difficult to effectively solve the problem of limited application of high-titanium slag aggregate in concrete, especially its impact on the workability, strength and durability of concrete is unknown, and the existing mix ratio design method is inefficient, so a lot of experiments and adjustments are required. .
Using the high-titanium slag aggregate concrete mix design method based on aggregate characteristics, the dry water absorption rate of saturated surfaces of high-titanium slag sand and stone is determined according to the close packing theory and the improved Bolomey formula. Optimize the concrete ratio with water.
The performance optimization of high-titanium slag aggregate concrete has been achieved, the working performance, strength and durability of concrete has been improved, the mix ratio design process has been simplified, and the design efficiency and resource utilization have been improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete design, and in particular to a high-titanium slag aggregate concrete mix design method based on aggregate properties. Background Art
[0002] High-titanium slag is an industrial byproduct of iron smelting in the Panxi region, with a large amount of emissions. Burying or piling it not only pollutes the environment and occupies land, but also wastes slag resources. It is urgently needed to be properly and effectively disposed of. Applying high-titanium slag as aggregate in concrete can save and replace primary resources and effectively reduce carbon emissions. It is one of the important measures to achieve high-quality development of building materials.
[0003] However, studies have shown that the addition of titanium slag aggregate will significantly reduce the workability of concrete, limiting its application. In addition, the current mix design of high-titanium slag aggregate concrete still refers to the mix design method of ordinary concrete, so that its mix strength requires a large number of tests and trials. The relationship between the change in the dosage of high-titanium slag aggregate and the strength, workability, and durability cannot be clarified. As a solid waste and porous material, there is little research on the concrete mix design method based on the aggregate characteristics of high-titanium slag aggregate. Therefore, improving the utilization rate of high-titanium slag in concrete and clarifying the mix design method of high-titanium slag aggregate concrete are crucial for the resource disposal of solid waste and the sustainable development of the building materials industry.
[0004] In view of this, this application is hereby filed. Summary of the invention
[0005] In order to solve the problems of the above-mentioned prior art, the present invention provides a high-titanium slag aggregate concrete mix ratio design method based on aggregate properties, which fully considers the aggregate properties of high-titanium slag and can design high-titanium slag aggregate concrete that meets the performance requirements according to the required strength of concrete and the amount of high-titanium slag aggregate. The design method is simple and effective, saves time and labor, and provides a design basis for promoting the application of high-titanium slag.
[0006] The present invention is achieved through the following technical solutions:
[0007] The present invention provides a method for designing a mix ratio of high-titanium slag aggregate concrete based on aggregate properties, comprising the following steps:
[0008] S1, determine the saturated surface dry water absorption of high titanium slag sand, high titanium slag stone, ordinary sand and ordinary stone used in concrete raw materials;
[0009] S2, determining the gradation of sand and stone aggregates of the high-titanium slag aggregate concrete according to the close packing theory;
[0010] S3, determining the slurry volume and aggregate volume according to the aggregate void ratio and surplus slurry generated by the aggregate accumulation;
[0011] S4, according to the improved Bolomey formula of the saturated surface dry water absorption rate of high-titanium slag aggregate, the water-binder ratio is determined, and the high-titanium slag aggregate concrete mix ratio based on aggregate properties is obtained.
[0012] In a specific embodiment, in step S1, the fineness modulus of the high-titanium slag sand is 2.4-2.8, and the slag powder content is less than 18%.
[0013] In a specific embodiment, in step S1, the single-stage crushing value of the high-titanium slag sand is <10%, and the water absorption rate is <3%.
[0014] In a specific embodiment, in step S1, the crushing value of the high-titanium slag is <12%, and the water absorption rate is <4%.
[0015] In a specific embodiment, in step S3, the method for obtaining the slurry volume comprises the following steps:
[0016] S31, optimize the sand and stone aggregates in high-titanium slag aggregate concrete according to the close packing theory, determine the ratio of sand and stone aggregates, and measure the aggregate void ratio of the optimized aggregates in combination with "Crushed Stone and Pebbles for Construction" (GB / T14685-2022);
[0017] S32, determining the paste volume and aggregate volume according to the absolute volume method, the aggregate void ratio and the surplus paste volume.
[0018] In a specific embodiment, in step S32, the calculation formula of the absolute volume method is as follows:
[0019] V A +V e +V k =1
[0020] Among them, V A is the aggregate volume, V e is the excess slurry volume, V k Aggregate void ratio after aggregate grading optimization.
[0021] In a specific embodiment, in step S32, the calculation formula of the surplus slurry volume is as follows:
[0022] V e =αV A
[0023] Among them, α is the surplus slurry coefficient, which is related to the aggregate volume and its value is 0.009~0.018.
[0024] In a specific embodiment, in step S4, when the amount of high-titanium slag sand and high-titanium slag stone is less than or equal to 50% of the amount of concrete aggregate, the specific method of improving the Bolomey formula is to use the following formula for improvement:
[0025]
[0026] Among them, f c is the concrete mix strength, B α is the amount of cementitious material, W e is the characteristic water consumption of high titanium slag aggregate, W j is the baseline water consumption, σ c , τ are constants related to cement type and curing age, see "Ordinary Concrete Mix Design Code" (JGJ55-2011) for details. After the amount of cementitious material is calculated by the above formula, the water-cement ratio can be calculated.
[0027] In a specific embodiment, the W e The calculation formula is as follows:
[0028]
[0029] Among them, ω t ,ω tt are the saturated surface dry water absorption rates of high-titanium slag sand and high-titanium slag stone respectively; ω j ,ω s are the saturated surface dry water absorption rates of ordinary sand and stone respectively; They are the aggregate dosage of high-titanium slag sand and high-titanium slag stone respectively.
[0030] In a specific embodiment, in step S4, when the amount of high-titanium slag sand and high-titanium slag stone is greater than 50% of the amount of concrete aggregate, the specific method of improving the Bolomey formula is to use the following formula for improvement:
[0031]
[0032] Among them, f c is the concrete mix strength, B α is the amount of cementitious material, W j is the baseline water consumption, σ c , τ are constants related to cement type and curing age. For details, see "Code for Design of Ordinary Concrete Mix Proportion" (JGJ55-2011).
[0033] In a specific implementation, in step S4, after the water-binder ratio of the concrete is determined, the required amount of water reducing agent is determined according to the workability of the concrete.
[0034] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0035] 1. A high-titanium slag aggregate concrete mix ratio design method based on aggregate properties provided in an embodiment of the present invention fully considers the aggregate properties of high-titanium slag, and can design high-titanium slag aggregate concrete that meets the performance requirements according to the required strength of concrete and the amount of high-titanium slag aggregate. The design method is simple and effective, saves time and effort, and provides a design basis for promoting the application of high-titanium slag;
[0036] 2. The high-titanium slag aggregate concrete mix ratio design method based on aggregate properties provided by the embodiment of the present invention is easy to operate and highly efficient. From the perspectives of comprehensive utilization of high-titanium slag, low-carbon concrete production technology, economy and environmental protection, it has significant social, economic and environmental benefits and is highly practical.
[0037] 3. An embodiment of the present invention provides a method for designing a high-titanium slag aggregate concrete mix ratio based on aggregate properties. The concrete prepared by the designed concrete mix ratio has good working performance, high strength, excellent durability and stable comprehensive performance. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0039] In the following description, a large number of specific details are set forth in order to provide a thorough understanding of the present invention. However, it is apparent to one of ordinary skill in the art that these specific details need not be employed to practice the present invention. In other embodiments, in order to avoid confusing the present invention, well-known materials or methods are not specifically described.
[0040] Throughout the specification, references to "one embodiment," "an embodiment," "an example," or "an example" mean that a particular feature, structure, or characteristic described in conjunction with the embodiment or example is included in at least one embodiment of the present invention. Therefore, the phrases "one embodiment," "an embodiment," "an example," or "an example" appearing in various places throughout the specification do not necessarily all refer to the same embodiment or example. In addition, particular features, structures, or characteristics may be combined in one or more embodiments or examples in any suitable combination and / or subcombination. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0041] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0042] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0043] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0044] Example 1
[0045] The embodiment of the present invention provides a method for designing a mix ratio of high-titanium slag aggregate concrete based on aggregate properties, comprising the following steps:
[0046] S1, determine the saturated surface dry water absorption of high titanium slag sand, high titanium slag stone, ordinary sand and ordinary stone used in concrete raw materials;
[0047] S2, determining the gradation of sand and stone aggregates of the high-titanium slag aggregate concrete according to the close packing theory;
[0048] S3, determining the slurry volume and aggregate volume according to the aggregate void ratio and surplus slurry generated by the aggregate accumulation;
[0049] S4, according to the improved Bolomey formula of the saturated surface dry water absorption rate of high-titanium slag aggregate, the water-binder ratio is determined, and the high-titanium slag aggregate concrete mix ratio based on aggregate properties is obtained.
[0050] In a specific embodiment, in step S1, the fineness modulus of the high-titanium slag sand is 2.4-2.8, and the slag powder content is less than 18%.
[0051] In a specific embodiment, in step S1, the single-stage crushing value of the high-titanium slag sand is <10%, and the water absorption rate is <3%.
[0052] In a specific embodiment, in step S1, the crushing value of the high-titanium slag is <12%, and the water absorption rate is <4%.
[0053] In a specific embodiment, in step S3, the method for obtaining the slurry volume comprises the following steps:
[0054] S31, optimizing the aggregates of titanium slag sand and titanium slag stone according to the close packing theory, determining the ratio of sand and gravel aggregates, and measuring the aggregate void ratio of the optimized aggregates in combination with Crushed Stone and Pebbles for Construction (GB / T14685-2022);
[0055] S32, determining the paste volume and aggregate volume according to the absolute volume method, the aggregate void ratio and the surplus paste volume.
[0056] In a specific embodiment, in step S32, the calculation formula of the absolute volume method is as follows:
[0057] V A +V e +V k =1
[0058] Among them, V A is the aggregate volume, V e is the excess slurry volume, V k Aggregate void ratio after aggregate grading optimization.
[0059] In a specific embodiment, in step S32, the calculation formula of the surplus slurry volume is as follows:
[0060] V e =αV A
[0061] Among them, α is the surplus slurry coefficient, which is related to the aggregate volume and its value is 0.009~0.018.
[0062] In a specific embodiment, in step S4, when the amount of high-titanium slag sand and high-titanium slag stone is less than or equal to 50% of the amount of concrete aggregate, the specific method of improving the Bolomey formula is to use the following formula for improvement:
[0063]
[0064] Among them, f c is the concrete mix strength, B α is the amount of cementitious material, W e is the characteristic water consumption of high titanium slag aggregate, W j is the baseline water consumption, σ c , τ are constants related to cement type and curing age, see "Ordinary Concrete Mix Design Code" (JGJ55-2011) for details. After the amount of cementitious material is calculated by the above formula, the water-cement ratio can be calculated.
[0065] In a specific embodiment, the W e The calculation formula is as follows:
[0066]
[0067] Among them, ω t ,ω tt are the saturated surface dry water absorption rates of high-titanium slag sand and high-titanium slag stone respectively; ω j ,ω s are the saturated surface dry water absorption rates of ordinary sand and stone respectively; They are the aggregate dosage of high-titanium slag sand and high-titanium slag stone respectively.
[0068] In a specific embodiment, in step S4, when the amount of high-titanium slag sand and high-titanium slag stone is greater than 50% of the amount of concrete aggregate, the specific method of improving the Bolomey formula is to use the following formula for improvement:
[0069]
[0070] Among them, f c is the concrete mix strength, B α is the amount of cementitious material, W j is the baseline water consumption, σ c , τ are constants related to cement type and curing age. For details, see "Code for Design of Ordinary Concrete Mix Proportion" (JGJ55-2011).
[0071] In a specific implementation, in step S4, after the water-binder ratio of the concrete is determined, the required amount of water reducing agent is determined according to the workability of the concrete.
[0072] Example 2
[0073] The embodiment of the present invention provides a method for designing a mix ratio of high-titanium slag aggregate concrete based on aggregate properties, and designs C30 concrete.
[0074] The high-titanium slag sand used in this embodiment has a fineness modulus of 2.6, a slag powder content of 16%, a single-stage crushing value of 4.7%, and a saturated surface dry water absorption rate of 2.6%; high-titanium slag stone: 5-25mm continuous grading, a crushing value of 11.6%, and a saturated surface dry water absorption rate of 3.8%; granite machine-made sand: fineness modulus 2.6, apparent density 2660kg / m 3 , saturated surface dry water absorption rate 0.6%; granite crushed stone: 5-25mm continuous grading, apparent density 2660kg / m 3 , saturated surface dry water absorption rate 0.8%. Cement density 3100kg / m 3 ,28d mortar compressive strength 52MPa; S95 mineral powder density 2890kg / m 3 ; Grade I fly ash density 2400kg / m 3 ;Concrete water density 1000kg / m 3 .
[0075] In this embodiment, 0% high-titanium slag sand and 0% high-titanium slag stone are added, wherein S95 ore powder accounts for 12% and Class I fly ash accounts for 30% in the cementitious material; the ratio of granite machine-made sand and crushed stone after grading optimization is 1:1.22, and the aggregate void ratio after grading optimization is measured to be 29.2%. α is taken as 0.014, then
[0076] V A +0.014V A =1-0.292; V A =0.698,V e +V k =0.302,
[0077] m 砂 =836,m 石 =1021
[0078] Among them, m 石 、m 砂 , 石 , 砂 They are the amount of stone (kg), the amount of sand (kg), the apparent density of stone (kg / m 3 ), sand apparent density (kg / m 3 ).
[0079] according to Combined with the "Ordinary Concrete Mix Design Code" (JGJ55-2011), but
[0080] Where m 水泥 =0.58B α ,m 矿粉 =0.12B α , m 粉煤灰 =0.3B α , m 水 =0.49B α ;
[0081] Then there is B α =360,m 水泥 =209,m 矿粉 =43,m 粉煤灰 =108,m 水 =176
[0082] Among them, m 水泥 、m 矿粉 、m 粉煤灰 、m 水 , 水泥 , 矿粉 , 粉煤灰 , 水 They are cement dosage (kg), mineral powder dosage (kg), fly ash dosage (kg), water dosage (kg), cement density (kg / m 3 ), mineral powder density (kg / m 3 ), fly ash density (kg / m 3 ), water density (kg / m 3 ).
[0083] The cement content is 209kg / m 3 , mineral powder dosage 43kg / m 3 , fly ash 108kg / m 3 , machine-made sand 836kg / m 3 , crushed stone 1021kg / m 3 , water consumption 176kg / m 3 , the admixture is determined according to the workability to be 6.5kg / m 3 .
[0084] Example 3
[0085] The embodiment of the present invention provides a method for designing a mix ratio of high-titanium slag aggregate concrete based on aggregate properties, and designs C30 concrete.
[0086] The high-titanium slag sand used in this embodiment has a fineness modulus of 2.6, a slag powder content of 16%, a single-stage crushing value of 4.7%, and a saturated surface dry water absorption rate of 2.6%; high-titanium slag stone: 5-25mm continuous grading, a crushing value of 11.6%, and a saturated surface dry water absorption rate of 3.8%; granite machine-made sand: fineness modulus 2.6, apparent density 2660kg / m 3 , saturated surface dry water absorption rate 0.6%; granite crushed stone: 5-25mm continuous grading, apparent density 2660kg / m 3 , saturated surface dry water absorption rate 0.8%. Cement density 3100kg / m 3 ,28d mortar compressive strength 52MPa; S95 mineral powder density 2890kg / m 3 ; Grade I fly ash density 2400kg / m 3 ;Concrete water density 1000kg / m 3 .
[0087] In this embodiment, 75% high-titanium slag sand and 0% high-titanium slag stone are added. The ratio of sand and stone in the concrete after optimization is 1:1.13, wherein S95 slag powder accounts for 12% and Class I fly ash accounts for 30% in the cementitious material; the aggregate void ratio after optimization is measured to be 30.4%, and α is taken as 0.014, then
[0088] V A +0.014V A =1-0.304; V A =0.686,V e +V k =0.314,
[0089] m 砂 =228,m 石 =1030,m 钛矿渣砂 =685
[0090] Among them, m 石 、m 砂 、m 钛矿渣砂 , 石 , 砂 , 钛矿渣砂 They are the amount of stone (kg), the amount of sand (kg), the amount of titanium slag sand (kg), the apparent density of stone (kg / m 3 ), sand apparent density (kg / m 3 ), apparent density of titanium slag sand (kg / m 3 ).
[0091] according to Combined with the "Ordinary Concrete Mix Design Code" (JGJ55-2011),
[0092] Where m 水泥 =0.58B α ,m 矿粉 =0.12B α , m 粉煤灰 =0.3B α , m 水 =0.54B α ;
[0093] Then there is B α =353,m 水泥 =205,m 矿粉 =42, m 粉煤灰 =106,m 水 =190
[0094] Among them, m 水泥 、m 矿粉 、m 粉煤灰 、m 水 , 水泥 , 矿粉 , 粉煤灰 , 水 They are cement dosage (kg), mineral powder dosage (kg), fly ash dosage (kg), water dosage (kg), cement density (kg / m 3 ), mineral powder density (kg / m 3 ), fly ash density (kg / m 3 ), water density (kg / m 3 ).
[0095] The cement content is 205kg / m 3 , mineral powder dosage 42kg / m 3 , fly ash 106kg / m 3 , machine-made sand 228kg / m 3 , high titanium slag sand 685kg / m 3 , crushed stone 1030kg / m 3 , water consumption 190kg / m 3 , admixture 6.5kg / m 3 .
[0096] Example 4
[0097] The embodiment of the present invention provides a method for designing a mix ratio of high-titanium slag aggregate concrete based on aggregate properties, and designs C30 concrete.
[0098] The high-titanium slag sand used in this embodiment has a fineness modulus of 2.6, a slag powder content of 16%, a single-stage crushing value of 4.7%, and a saturated surface dry water absorption rate of 2.6%; high-titanium slag stone: 5-25mm continuous grading, a crushing value of 11.6%, and a saturated surface dry water absorption rate of 3.8%; granite machine-made sand: fineness modulus 2.6, apparent density 2660kg / m 3 , saturated surface dry water absorption rate 0.6%; granite crushed stone: 5-25mm continuous grading, apparent density 2660kg / m 3 , saturated surface dry water absorption rate 0.8%. Cement density 3100kg / m 3 ,28d mortar compressive strength 52MPa; S95 mineral powder density 2890kg / m 3 ; Grade I fly ash density 2400kg / m 3 ;Concrete water density 1000kg / m 3 .
[0099] In this embodiment, 100% high-titanium slag sand and 0% high-titanium slag stone are added. The ratio of sand and stone in the concrete after optimization is 1:1.08, wherein S95 slag powder accounts for 12% and Class I fly ash accounts for 30% in the cementitious material; the aggregate void ratio after optimization is measured to be 31.1%, and α is taken as 0.014, then
[0100] V A +0.014V A =1-0.311; V A =0.679,V e +V k =0.321,
[0101] m 石 =1000, m 钛矿渣砂 =926
[0102] Among them, m 石 、m 钛矿渣砂 , 石 , 钛矿渣砂 They are the amount of stone (kg), the amount of titanium slag sand (kg), the apparent density of stone (kg / m 3 ), apparent density of titanium slag sand (kg / m 3 ).
[0103] according to Combined with the "Ordinary Concrete Mix Design Code" (JGJ55-2011),
[0104] Where m 水泥 =0.58B α ,m 矿粉 =0.12Bα , m 粉煤灰 =0.3B α , m 水 =0.54B α ;
[0105] Then there is B α =360,m 水泥 =209,m 矿粉 =43,m 粉煤灰 =108,m 水 =194
[0106] Among them, m 水泥 、m 矿粉 、m 粉煤灰 、m 水 , 水泥 , 矿粉 , 粉煤灰 , 水 They are cement dosage (kg), mineral powder dosage (kg), fly ash dosage (kg), water dosage (kg), cement density (kg / m 3 ), mineral powder density (kg / m 3 ), fly ash density (kg / m 3 ), water density (kg / m 3 ).
[0107] The cement content is 209kg / m 3 , mineral powder dosage 43kg / m 3 , fly ash 108kg / m 3 , machine-made sand 0kg / m 3 , high titanium slag sand 926kg / m 3 , crushed stone 1000kg / m 3 , water consumption 194kg / m 3 , admixture 6.5kg / m 3 .
[0108] Example 5
[0109] The embodiment of the present invention provides a method for designing a mix ratio of high-titanium slag aggregate concrete based on aggregate properties, and designs C30 concrete.
[0110] The high-titanium slag sand used in this embodiment has a fineness modulus of 2.6, a slag powder content of 16%, a single-stage crushing value of 4.7%, and a saturated surface dry water absorption rate of 2.6%; high-titanium slag stone: 5-25mm continuous grading, a crushing value of 11.6%, and a saturated surface dry water absorption rate of 3.8%; granite machine-made sand: fineness modulus 2.6, apparent density 2660kg / m 3 , saturated surface dry water absorption rate 0.6%; granite crushed stone: 5-25mm continuous grading, apparent density 2660kg / m3 , saturated surface dry water absorption rate 0.8%. Cement density 3100kg / m 3 ,28d mortar compressive strength 52MPa; S95 mineral powder density 2890kg / m 3 ; Grade I fly ash density 2400kg / m 3 ;Concrete water density 1000kg / m 3 In this embodiment, 0% high-titanium slag sand and 75% high-titanium slag stone are added. The ratio of sand and stone in the concrete after optimization is 1:1.17, in which S95 slag powder accounts for 12% and Class I fly ash accounts for 30% in the cementitious material. The aggregate void ratio after optimization is 32.0%, and α is 0.014.
[0111] V A +0.014V A =1-0.320; V A =0.671,V e +V k =0.330,
[0112] m 钛矿渣石 =767,m 石 =256,m 砂 =874
[0113] Among them, m 石 、m 砂 、m 钛矿渣石 , 石 , 砂 , 钛矿渣石 They are the amount of stone (kg), the amount of sand (kg), the amount of titanium slag (kg), the apparent density of stone (kg / m 3 ), sand apparent density (kg / m 3 ), apparent density of titanium slag (kg / m 3 ).
[0114] according to Combined with the "Ordinary Concrete Mix Design Code" (JGJ55-2011),
[0115] Where m 水泥 =0.58B α ,m 矿粉 =0.12B α , m 粉煤灰 =0.3B α , m 水 =0.54B α ;
[0116] Then there is B α=370,m 水泥 =215,m 矿粉 =44,m 粉煤灰 =111,m 水 =199
[0117] Among them, m 水泥 、m 矿粉 、m 粉煤灰 、m 水 , 水泥 , 矿粉 , 粉煤灰 , 水 They are cement dosage (kg), mineral powder dosage (kg), fly ash dosage (kg), water dosage (kg), cement density (kg / m 3 ), mineral powder density (kg / m 3 ), fly ash density (kg / m 3 ), water density (kg / m 3 ).
[0118] The cement content is 215kg / m 3 , mineral powder dosage 44kg / m 3 , fly ash 111kg / m 3 , machine-made sand 874kg / m 3 , high titanium slag sand 0kg / m 3 , crushed stone 256kg / m 3 , high titanium slag 767kg / m 3 , water consumption 199kg / m 3 , admixture 6.5kg / m 3 .
[0119] The mix proportions of the concrete components obtained by the mix proportion design methods of Examples 2 to 5 are shown in Table 1, and the corresponding properties of the concrete obtained by the mix proportions of the examples are shown in Table 2.
[0120] Table 1
[0121]
[0122] Table 2
[0123]
[0124] In summary, the high-titanium slag aggregate concrete mix ratio design method based on aggregate properties provided by the present invention fully considers the aggregate properties of high-titanium slag, and can design high-titanium slag aggregate concrete that meets the performance requirements according to the required strength of concrete and the amount of high-titanium slag aggregate. The design method is simple and effective, saves time and labor, and provides a design basis for promoting the application of high-titanium slag. The concrete prepared by the designed concrete mix ratio has good working performance, good fluidity, high strength, excellent durability, good economy, and stable comprehensive performance. It can be used in municipal bridges, prefabricated components and other engineering structures and is widely used.
[0125] The mix design method of the present invention can reasonably and effectively dispose of high-titanium slag, can significantly reduce the cost of products, and is one of the ways for low-carbon, green and sustainable development of the construction industry.
[0126] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for designing the mix ratio of high-titanium slag aggregate concrete based on aggregate properties, characterized in that: The steps include: S1, determine the saturated surface dry water absorption of high titanium slag sand, high titanium slag stone, ordinary sand and ordinary stone used in concrete raw materials; S2, determining the gradation of sand and stone aggregates of the high-titanium slag aggregate concrete according to the close packing theory; S3, determining the slurry volume and aggregate volume according to the aggregate void ratio and surplus slurry generated by the aggregate accumulation; S4, according to the improved Bolomey formula of the saturated surface dry water absorption rate of high-titanium slag aggregate, the water-binder ratio is determined, and the high-titanium slag aggregate concrete mix ratio based on aggregate properties is obtained.
2. The method for designing the mix ratio of high-titanium slag aggregate concrete based on aggregate properties according to claim 1 is characterized in that: In step S1, the fineness modulus of the high-titanium slag sand is 2.4-2.8, and the slag powder content is less than 18%.
3. The method for designing the mix ratio of high-titanium slag aggregate concrete based on aggregate properties according to claim 1, characterized in that: In step S1, the single-stage crushing value of the high-titanium slag sand is less than 10%, and the water absorption rate is less than 3%.
4. The method for designing the mix ratio of high-titanium slag aggregate concrete based on aggregate properties according to claim 1, characterized in that: In step S1, the crushing value of the high-titanium slag is less than 12%, and the water absorption rate is less than 4%.
5. The method for designing the mix ratio of high-titanium slag aggregate concrete based on aggregate properties according to claim 1, characterized in that: In step S3, the method for obtaining the slurry volume comprises the following steps: S31, optimizing the sand and stone aggregates in the high-titanium slag aggregate concrete according to the close packing theory, determining the ratio of sand and stone aggregates, and measuring the aggregate void ratio of the optimized aggregates; S32, determining the paste volume and aggregate volume according to the absolute volume method, the aggregate void ratio and the surplus paste volume.
6. A method for designing a high titanium slag aggregate concrete mix ratio based on aggregate properties according to claim 5, characterized in that: In step S32, the calculation formula of the absolute volume method is as follows: V A +V e +V k =1 Among them, V A is the aggregate volume, V e is the excess slurry volume, V k Aggregate void ratio after aggregate grading optimization.
7. The method for designing the mix ratio of high-titanium slag aggregate concrete based on aggregate properties according to claim 5, characterized in that: In step S32, the calculation formula of the surplus slurry volume is as follows: V e =αV A Among them, α is the surplus slurry coefficient, which is related to the aggregate volume and its value is 0.009~0.
018.
8. The method for designing the mix ratio of high-titanium slag aggregate concrete based on aggregate properties according to claim 1, characterized in that: In step S4, when the amount of high-titanium slag sand and high-titanium slag stone is less than or equal to 50% of the amount of concrete aggregate, the specific method of improving the Bolomey formula is to use the following formula for improvement: Among them, f c is the concrete mix strength, B α is the amount of cementitious material, W e is the characteristic water consumption of high titanium slag aggregate, W j is the baseline water consumption, σ c , τ are constants related to cement type and curing age.
9. The method for designing the mix ratio of high-titanium slag aggregate concrete based on aggregate properties according to claim 7, characterized in that: The W e The calculation formula is as follows: Among them, ω t ,ω tt are the saturated surface dry water absorption rates of high-titanium slag sand and high-titanium slag stone respectively; ω j ,ω s are the saturated surface dry water absorption rates of ordinary sand and stone respectively; They are the aggregate dosage of high-titanium slag sand and high-titanium slag stone respectively.
10. The method for designing the mix ratio of high-titanium slag aggregate concrete based on aggregate properties according to claim 1, characterized in that: In step S4, when the amount of high-titanium slag sand and high-titanium slag stone is greater than 50% of the amount of concrete aggregate, the specific method of improving the Bolomey formula is to use the following formula for improvement: Among them, f c is the concrete mix strength, B α is the amount of cementitious material, W j is the baseline water consumption, σ c , τ are constants related to cement type and curing age.